Can Financial Soundness Indicators Help Predict Financial Sector Distress? - Pietrzak, Marcin (IMF Working Papers; Working Paper ;, 2021)
This paper shows how the role of Financial Soundness Indicators (FSIs) in financial surveillance can be usefully enhanced. Drawing from different statistical techniques, the paper illustrates that FSIs generate signals that can accurately detect, with 4 to 12 quarters lead, emerging financial distress-as measured by tight financial conditions.